Model Pemasaran Ternak Sapi di Kecamatan Praya Timur Pasca Program Bumi Sejuta Sapi di Nusa Tenggara Barat - Zulkarnaen Zulkarnaen (Valid: Jurnal Ilmiah, 2020)
After Bumi Sejuta Sapi (BSS) program in NTB, cattle farmers are required to determine the marketing patterns of their animals, where female cattle cannot be traded easily, especially intended for consumption. This research is conducted to find out the cattle marketing model in the Praya Timur District after the Bumi Sejuta Sapi program. This study uses a qualitative approach with explorative descriptive methods. The location of the study was conducted in Praya Timur District, Central Lombok Regency. The data analysis model used is the Miles and Huberman model analysis, where the data that has been categorized, and interpreted subsequently is described in a model. The results of this study indicate that the livestock marketing model in the Praya Timur District is not much different from the previous livestock marketing model where farmers are free to sell their livestock in the animal market, to slaughterhouses, other breeders, or to other traders. The difference is that for recipients of livestock assistance from the BSS program, sales of cattle may only be done if they have given birth at least twice; The sale of female cattle outside the area is not permitted; and Prohibition of slaughter of cattle that are still productive